Pengaruh Konsep Menabung Dengan Sistem Lumbung Padi Terhadap Kesejahteraan Masyarakat Menurut Perspektif Ekonomi Islam Di Desa Citorek - budiman budiman; Deden Hidayat (e-Jurnal Aksioma Al-Musaqoh : Journal of Islamic Economics and Business Studies, 2021)
In general, Wewengkon Citorek is surrounded by mountains and resembles a valley, with its strategic location on flat and wide land surrounded by high mountains. The majority of the community's livelihood is farming (not farm labor). To fulfill the needs of life, both clothing and food, the community generally relies on agricultural products, especially agriculture in the field of rice (sawah) which is only harvested for one year. In addition, there are also people who work in trade or other economic activities. Until now, rice as an agricultural product is the main priority for the life of the Citorek community and is a superior commodity. From the above, it can be concluded that the level of economic capability of the community can be divided into three phases, namely 30% of the community is well-off, 40% of the community is moderately well-off, less well-off and below the poverty line reaches 30%. This is due to the unavailability of jobs that can open up the community's economic path. The discussion in this research can be formulated as follows: How is the saving system with rice barns done by the middle citorek community and how much influence it has on the welfare of the community. This research aims to find out the system of saving rice barns in the village of Central Citorek and the extent of its influence on community welfare. It is seen from the opinion that is stored in the barn. The data used in this study are primary data obtained from direct research results by means of intervew. Then the data that has been obtained is processed using SPSS.16.00. and the analysis used is simple regression analysis with the Ordinary Least Square (OLS) method. From the results of the analysis and processing of Spss.16.00, it is concluded that the system of saving with rice granaries on the welfare of the community has a very high relationship, namely, 0.994 is above 0.90 and this is in accordance with 66% of the people of Citorek Tengah Village out of 100% are farmers. and the effect of saving with rice granaries affects welfare up to 98.8% and the other 1.2% is influenced by variables outside the study, namely traders, services and craftsmen. thus it can be seen how much influence saving with the rice granary system on community welfare. Keywords: Saving, Management, Lumpung Padi, Welfare